Electronic Information Systems in Sci-Tech Libraries, 1st edition - Steinke, Cynthia A. (Routledge, 2020)
This book, first published in 1990, analyses the variety of ways in which libraries extend their resources to users beyond the physical walls of their organization. Librarians discuss the concept of the library as more than just a place - since its holdings can now appear on the screen of users’ computers in the same city or in a city hundreds of miles away - but rather as a force that electronically links users directly with both local and remote sources of information. Six informative chapters examine electronic information systems and document delivery from the local collection to the workplace, between system libraries and from non-library sources. Readers can look first hand at some of the most sophisticated and widespread systems in the country, including four academic libraries that promote electronic services to remote users and two special libraries offering innovative services. The authoritative contributing authors also forecast new systems and services.